Analisis Kualitas Pertanyaan Mahasiswa Calon Guru Rumpun Ilmu Pengetahuan Alam Ditinjau dari Pengalaman Belajar - Wisnu Juli Wiono; Pramudiyanti Pramudiyanti; Nadya Meriza (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2021)
The quality of the question can describe the development of a person's thinking level. The questioning activity is also an indication that a student is actively involved in the learning process. The purpose of this study was to describe the quality profile of the students' questions from a natural science family in terms of their learning experience. This study uses a descriptive method because it aims to describe the profile of research subjects. The research instrument was a learning experience questionnaire and a question matrix. Learning experience questionnaires are used to reveal a picture of student learning experiences during lectures. Meanwhile, the question matrix is used to measure the level of thinking on each question made by students. The population of this study were all students in the Mathematics and Natural Sciences Education Department who had attended Basic Biology courses. Data analysis using simple regression shows that student learning experience does not significantly influence the quality of student questions. Each study program has a t score of 0.120 (chemistry education); 1,341 (Physics education); and 0.578 (Biology education). The entire t score is less than the t table. This condition is strongly suspected because the core activity phase of the lecture process did not go well. Based on the data analysis, it was found that the core activity phase had the lowest score of 67.33 which was significant.